Proposal of an accompaniment program to High Performance Student Athletes: Advances in the commitment of the Faculty of Physical Culture, USTA Sports and Recreation in training professional athletes (Impetus, 2021)
Based on two research projects (2013) it was identified that Colombian universities do not have a training model that responds to the particular needs of student athletes from harmonize your academic and sports life, so with They must often give up any of these activities. The different strategies that offer international higher education institutions for the access, permanence and graduation of athletes. These results together with the experience in the Faculty of Physical Culture of the USTA to receive among its students high-performance athletes and recognition of the legal and institutional framework that would favor their inclusion and permanence, are the basis of the proposal presented. This raises a concept of student athlete of high level, requirements, enrollment process, strategies support in admission, enrollment and academic monitoring, specialized counseling, flexibility of calendars, appropriate methodological and evaluative modalities, virtuality, networking with the sports organization and its coaches, alternative options in degree work and / or professional practices, psychological support and time organization, financial support, recognition social, preparation for working life